Peningkatan Hasil Belajar PPKN Siswa Kelas VIII.6 SMP Negeri 43 Palembang melalui Model Pembelajaran Learning Together - Driana, Leni Yarti (Lentera: Jurnal Ilmiah Kependidikan, 2022)
A conscious effort education that is deliberately designed to achieve the stated goals. The results of PPKN learning in class VIII.6 SMP Negeri 43 Palembang are still low. The results of the first PPKN daily test only reached an average of 64.38 and only 46.88% of students achieved a score of 70 or >70. Whereas ideally, at least 85% of students should get 70 or >70. The low PPKN test results are caused by the teacher still not maximal in teaching the material to students. The teacher does not update the old learning model or still uses learning that is still focused on teachers who are actively lecturing. Teachers have not mastered the way that is not right on how to motivate students so that learning outcomes can be further improved. Therefore, the learning outcomes of grade VIII.6 students of SMP Negeri 43 Palembang are still low and need improvement by using an attractive learning model for students. The formulation of the problem in this study is: "Can the Learning Together learning model improve PPKN learning outcomes in class VIII.6 students of SMP Negeri 43 Palembang?". The subjects in this study were students of Class VIII.6 SMP Negeri 43 Palembang, totaling 32 students. This research will be carried out in class VIII.6 from September to November 2019. This class action research has been said to be complete with the evidence of improving Civics learning outcomes using the Learning Together learning model. Mastery learning increased from pre-cycle, cycle I to cycle II, which were 46.88%, 65.63% and 87.50%, respectively. In cycle II, students' learning mastery classically had been achieved and experienced a very good increase.